Increasing Readiness to Grow Traffic Safety Culture and Adopt the Safe System Approach: A Story of the Washington Traffic Safety Commission - Otto, Jay; Ward, Nic; Finley, Kari; Baldwin, Shelly T.; Alonzo, Wade (Frontiers in Future Transportation, 2022)
Growing traffic safety culture and adopting the Safe System approach are strategies to support achieving a vision of zero traffic fatalities and serious injuries. However, adopting these strategies requires organizational change. Change is more likely to occur and be sustained by growing organizational readiness for change. Change readiness is driven by perceptions that (1) the change aligns with the organization's culture, (2) the organization (e.g., leadership, staff) is committed to the change, and (3) the organization has the resources necessary to make the change. The Washington Traffic Safety Commission has been engaged in a change process that focuses on growing traffic safety culture and adopting the Safe System approach for many years. This article shares insights from their journey that other organizations can use to bolster their own change efforts.